Respuesta :
Given that :-
- x = 4y +3
- y = -2x -3
To Find :-
- Value of x.y
Solution :-
→ x = 4y + 3 equation 1st
→ y = -2x -3 equation 2nd .
Now putting the value of x from first equation to second equation.
→ y = -2(4y +3 ) -3
→ y = -8y - 6 - 3
→ y + 8y = -9
→ 9y = -9
→ y = -1
Now putting the value of y in equation first .
→ x = 4(-1) + 3
→ x = -4 + 3
→ x = -1
Now multiply and X and y.
→ x.y = -1(-1)
→ x.y = 1 .
[tex]\huge {\bold {\star {\fcolorbox {black} {yellow} {Answer}}}} [/tex]
Given,
- x = 4y + 3 ⠀⠀⠀⠀⠀⠀ i
- y = -2x - 3⠀⠀⠀⠀⠀⠀⠀⠀ii
To find;
- The value of xy
[tex]{\boxed{\red{\underline{\sf{Solution:}}}}}[/tex]
Putting the value of x in ii, we get ;
➝ y = - 2(4y+3) - 3
➝ y = - 8y - 6 - 3
➝ y = - 8y - 9
➝ y + 8y = - 9
➝ 9y = - 9
∴ y = - 1
Putting the value of y in i, we get ;
➝ x = 4y + 3
➝ x = 4(-1) + 3
➝ x = - 4 + 3
∴ x = - 1
Now,
➛ xy = (- 1)(-1)
⛬ xy = 1